Identification and Management Strategies for Intracoronary High Thrombus Burden in Patients With STEMI: A Practical Experience and Literature Review - Xing Feng; Tongku Liu (Reviews in Cardiovascular Medicine)
Acute myocardial infarction (AMI) includes ST-segment elevation myocardial infarction (STEMI) and non-ST-segment elevation myocardial infarction (NSTEMI). STEMI is the most severe type of AMI and is a life-threatening disease. The onset and progress of STEMI are accompanied by thrombosis in coronary arteries, which leads to the occlusion of coronary vessels. The main pathogenesis of STEMI is the presence of unstable atherosclerotic plaques (vulnerable plaques) in the vessel wall of the coronary arteries. The vulnerable plaques may rupture, initiating a cascade of blood coagulation, ultimately leading to the formation and progression of thrombus. Treating STEMI patients with high thrombus burden is a challenging problem in the field of percutaneous coronary intervention (PCI). During the PCI procedure, the thrombus may be squeezed and dislodged, leading to a distal embolism in the infarction-related artery (IRA), resulting in slow blood flow (slow flow) or no blood flow (no reflow), which can enlarge the ischemic necrosis area of myocardial infarction, aggravate myocardial damage, endanger the life of the patient, and lead to PCI failure. Identifying and treating high thrombus burden in the IRA has been a subject of debate and is currently a focal point in research. Clinical strategies such as the use of thrombus aspiration catheters and antiplatelet agents (platelet glycoprotein IIb/IIIa receptor inhibitors, such as tirofiban), as well as the importance of early intervention to prevent complications, such as no reflow and in-stent thrombosis, are highlighted in recent studies. Thrombus aspiration is an effective therapeutic approach for removing intracoronary thrombus, thereby decreasing the incidence of slow flow/no reflow phenomena and enhancing myocardial tissue perfusion, ultimately benefiting from protecting heart function and improving the prognosis of STEMI patients. Notably, deferred stenting benefits STEMI patients with high thrombus burden and hemodynamic instability. Meanwhile, antithrombotic and thrombolytic agents serve as adjuvant therapies alongside PCI. Primary PCI and stenting are reasonable for patients with low intracoronary thrombus burden. The article describes the practical experience of the author and includes a literature review that details the research progress in identifying and managing STEMI patients with intracoronary high thrombus burden, and provides valuable insights into managing patients with high thrombus burden in coronary arteries. Finally, this article serves as a reference for clinicians.